Periradicular tissue necrosis caused by accidentally injected sodium hypochlorite through fausse route in upper maxillary canine - Pejanović Đorđe; Čabrilo Milana; Đurić Dušan; Biočanin Vladimir (Serbian Medical Society - Dental Section, Belgrade, 2020)
Sodium hypochlorite (NaOCl) is a strong antiseptic agent that is usually used as endodontic irrigant for dissolving organic parts of pulp and dentin and neutralizing toxic products. However, the use of sodium hypochlorite may cause destruction of blood vessels, soft tissues and bone necrosis if extruded into the periapical region. Urgent treatment of the NaOCl accident should be oriented on pain relief, infection control and recovery. This paper shows a case of periradicular tissue necrosis after accidental extrusion on NaOCl through fausse route of right maxillary canine, and complete tissue regeneration after surgical debridement and bone augmentation with addition of platelet rich fibrin (PRF) that occurred in a 53-year old patient at the dental clinic of Faculty of Dentistry in Pancevo.